Developing employability skills from service-learning experience at Putra Future Classroom (PFC) - Omar, Muhd Khaizer; Md Khambari, Mas Nida; Ma'rof, Aini Marina; Ismail, Ismi Arif; Tengku Kamalden, Tengku Fadilah; Ab. Jalil, Habibah; Salim, Siti Suria; Abd Rahim, Nur Aira; Alias, Siti Noormi; Mohd Puad, Mohd Hazwan; Muhamad, Mohd Mokhtar; Arshad, Mohd Mursyid (Human Resource Management Academic Research Society, 2018)
Service-learning imposes a practical dissemination of knowledge though hands-on practices and ‘learning-by-doing’. Often, service-learning has been misinterpreted with the concept of volunteerism where service-learning offer the application of theoretical knowledge which learned through traditional classroom then applying knowledge through volunteering work. The blending process of theoretical knowledge and practical learning environment produces meaningful learning experiences and tends to be more effective in remembering and skills-to work. We carried out a case study of 15 postgraduate students who experienced service-learning project at Putra Future Classroom at the Faculty of Educational Studies, Universiti Putra Malaysia. A specific project call “Earth Day” was organized in commemorating the annual earth day celebration around the world. The project involved a children age between four to six years old who experienced numerous activities related to earth day awareness campaign. This article explored narrative feedback through qualitative approach to discover postgraduate students’ experiences of organizing service-learning project and explore the learning experiences from theoretical knowledge learned in the traditional classroom for the course Program Evaluation in Technical and Vocational Education and Training (TVE5006 and EDU5443). At the end of the service-learning project, the students were asked to answer an open-ended qualitative question disseminated via JotForm, an online questionnaire platform during the process of qualitative data collection. All answers were recorded and later analysed thematically using a two-layer of constant comparative analysis method and triangulated with class assignments, obervations and reflection notes . The findings indicated seven themes that emerged from the analysis. Salient benefits of service-learning project for post graduate learning experiences to enhance their employability skills for the 21st century skills before entering employment market were suggested.